Analisis Quality of Service Jaringan WLAN Metode PPDIOO Pada Jurusan Kesehatan Gigi Poltekkes Tasikmalaya - Zahra Ramadhani Putri; Elsa Novia Safitri; Helmy Dzulfikar (Fakultas Ilmu Komputer dan Desain - Unsurya, 2026)
This study aims to evaluate the quality of WLAN network services at the Department of Dental Health, Poltekkes Tasikmalaya, which has a bandwidth of 150 Mbps but frequently experiences connectivity issues. The method used is PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) with Quality of Service (QoS) parameters based on the TIPHON standard. Measurements were conducted at 15 locations using the nPerf and Wireshark applications. Observation results indicate several critical points, such as the Auditorium and the D4 Faculty Room, fall into the